m-3m=-14-4m

Simple and best practice solution for m-3m=-14-4m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-3m=-14-4m equation:


Simplifying
m + -3m = -14 + -4m

Combine like terms: m + -3m = -2m
-2m = -14 + -4m

Solving
-2m = -14 + -4m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '4m' to each side of the equation.
-2m + 4m = -14 + -4m + 4m

Combine like terms: -2m + 4m = 2m
2m = -14 + -4m + 4m

Combine like terms: -4m + 4m = 0
2m = -14 + 0
2m = -14

Divide each side by '2'.
m = -7

Simplifying
m = -7

See similar equations:

| x^3=61.81 | | 1.5n-.5=n+3.25 | | -4(2x-2)=-(4x-4) | | Y^3+y^2-16y+16=0 | | -38=4(7+3p)+5(-2-p) | | -6-4x=26 | | 6k-5k+8k-4k= | | -x^3-6=-7 | | 2(5-2z)-2(4z+6)=z-8 | | -2(7k+4)+9=32 | | (-8)x(6)= | | (j-3)j+4+j=196 | | 16x+11x=y | | x^2=16-28 | | 7v+6-3v=2 | | 5x+2=7x-48 | | 5(x+6x)=40(3-4x) | | 3(2r+1)=26+6r | | 10-20x+x=9x-33 | | -12/7+x=48/7 | | (5)x(-2)= | | 20x+x=180 | | 2b+11=-15 | | -8=-10-2 | | 3x^2+4=2x^2+4 | | -7-(3n+6)=-4-6n | | 15-20y+14y=15-35y | | 2(y+8)=32 | | -5(8n+6)+8(-3-n)=-54 | | 211=11x+13(19-x) | | 4+5b-5b=4 | | 35=7b |

Equations solver categories